The development of the dynamics endurance in children and youth (foreign innovations) - Сергієнко, Л. П.; Лишевська, В. М. (Physical Education Theory and Methodology, 2012)
The article generalizes a foreign experience of the development of the dynamic strength endurance in children and youth. The technology of physical exercises which can be suggested for the development of the dynamic strength endurance of different muscular groups is described.